2019
DOI: 10.1007/s11695-018-3570-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy in Heart Failure Patients with Left Ventricular Assist Device

Abstract: Background: There is limited data in the literature evaluating outcomes of bariatric surgery in severely obese patients with left ventricular assist device (LVAD) as a bridge to make them acceptable candidates for heart transplantation. This study aims to assess the safety and effectiveness of laparoscopic sleeve gastrectomy (LSG) in patients with previously implanted LVAD at our institution. Methods: All the patients with end-stage heart failure (ESHF) and implanted LVAD who underwent LSG from2013 to January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Bariatric surgery in patients with severe cardiomyopathy, including LVAD, is an opportunity for rapid weight loss as a "bridge" to transplantation. Studies of small cohorts show patients with LVAD who underwent bariatric surgery had improvement in median left ventricular ejection fraction and reduction in NYHA classification [6,10] . In particular, Punchai et al [6] reported on three patients with LVAD who went on to receive a heart transplant after LSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bariatric surgery in patients with severe cardiomyopathy, including LVAD, is an opportunity for rapid weight loss as a "bridge" to transplantation. Studies of small cohorts show patients with LVAD who underwent bariatric surgery had improvement in median left ventricular ejection fraction and reduction in NYHA classification [6,10] . In particular, Punchai et al [6] reported on three patients with LVAD who went on to receive a heart transplant after LSG.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of small cohorts show patients with LVAD who underwent bariatric surgery had improvement in median left ventricular ejection fraction and reduction in NYHA classification [6,10] . In particular, Punchai et al [6] reported on three patients with LVAD who went on to receive a heart transplant after LSG. Acceptable rates of complications included five perioperative morbidities and two deaths from LVAD complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bariatric surgery is an option for patients with VADs to lose weight and improve HT candidacy, with some studies reporting promising results [ 5 7 ]. Over the last years, laparoscopic sleeve gastrectomy (LSG) has become the preferred bariatric surgery for obese patients with VADs due to its effectiveness and safety profile [ 8 ].…”
Section: Objectivementioning
confidence: 99%
“…Few small cohort studies and case reports have shown promising results of bariatric surgery (BS) in obese patients with VADs [3][4][5][6]. Nevertheless, much of the postoperative weight (and BMI) trends remains unknown in this population.…”
Section: Objectivementioning
confidence: 99%